Towards the propagation of a critically endangered tree species Anisoptera scaphula - Hossain, Md. Aktar; Ferdous, Jebin; M. Abdur Rahman,; Azad, Md. Abul Kalam; Ab. Shukor, Nor Aini (Polish Academy of Sciences, Institute of Dendrology, 2014)
Anisoptera scaphula (Roxb.) Kurz, the tallest tree species in Bangladesh, is critically endangered worldwide due to its poor natural regeneration. This study describes the appropriate regeneration technique for A. scaphula through seed germination and clonal propagation by stem cutting. The fastest and highest germination percentage (65) was observed in dewinged seeds sown inverted orientation with half buried position (T10) followed by dewinged seeds (62.5%) sown horizontally in full buried (T7) and delayed germination with lowest percentage (15) was in control (T0). Optimum initial growth was also shown when seedlings were developed from the seeds under T7. Both winged and dewinged seeds sown vertically in full buried or half buried position produced curved seedlings. However, dewinged seeds sown in horizontal or inverted (winged side down) position produced otherwise i.e., straight seedlings. The highest rooting percentages (63%) and maximum number of root (4.8) per cutting were obtained when one node cuttings treated with 0.8% IBA solution followed by 0.4% IBA in turn affecting for better survival and growth of rooted cuttings in the nursery conditions.